Quality Control of SIR 20 Product Using The Statistical Quality Control (SQC) At PT. WLK - Hairiyah, Nina; Rizki Amalia, Raden; Nuryati, Nuryati (Jurnal Teknologi Agro-Industri, 2024)
Good quality is an important requirement for companies to gain competitiveness in their products on the market. PT. WLK is a company that produces SIR 20 rubber, which is currently experiencing quality problems such as white spot product defects and contamination that does not meet established quality standards. The aim of this research is to analyze the quality control of SIR 20 products at PT.WLK using the Statistical Quality Control (SQC) approach. This quality control analysis is carried out using statistical tools in the form of check sheets, P control charts, Pareto diagrams and fishbone diagrams. The results of the research carried out show that white spots are caused by several factors, namely humans, machines, environment and methods, while contamination is caused by humans, machines and materials so that it does not meet quality standards. Good quality standards, namely the absence of product defects such as white spots and contamination. Based on the results of research carried out using cause and effect diagrams, factors that cause product defects can be identified, such as human factors that are not careful enough, raw materials that are handled poorly, machines that do not receive enough maintenance, work method factors that often occur deviations in work implementation, and weather factors that often change.